Recognition and production of emotions in children with cochlear implants - Mildner, Vesna (Array, 2014)
The aim of this study was to examine auditory recognition and vocal production of emotions in three prelingually bilaterally profoundly deaf children aged 6–7 who received cochlear implants before age 2, and compare them with age-matched normally hearing children. No consistent advantage was found for the normally hearing participants. In both groups, sadness was recognized best and disgust was the most difficult. Confusion matrices among other emotions (anger, happiness, and fear) showed that children with and without hearing impairment may rely on different cues. Both groups of children showed that perception is superior to production. Normally hearing children were more successful in the production of sadness, happiness, and fear, but not anger or disgust. The data set is too small to draw any definite conclusions, but it seems that a combination of early implantation and regular auditory–oral-based therapy enables children with cochlear implants to process and produce emotional content comparable with children with normal hearing.